(untitled) (Journal of Fiber Bioengineering and Informatics, 2024)
The traditional apparel industry faces challenges to the quarantine of the global COVID-19 pandemic dramatically. The AI technics provide promising solutions for the apparel industry shift from labour-intensive to technic-intensive for survival. However, there are many open problems on how AI could find its application in mass customization. This paper presents practicable methods, frameworks and the curial technologies of AI-promoted apparel mass customization. The AI cloud will apply in traditional knowledge management of customers (KM) with which AI cloud has been trained and make predication of trends and customer’s preferences and enable personalized AI recommendations. With AI measurement flexible digital research development techniques can automatically generate personalized patterns and virtual garment prototypes based on different body shapes. By using the RFID label, the AI cloud could easily provide quality control, products tracing back in the production process and AI logistics. Those solutions and key technologies will benefit the process of apparel industry 4.0.